Gastric Deserosalization: What Lies Behind Closed Doors - Prabudh Goel; Minu Bajpai; Murli Krishna Nagendla; Akhil Singh (Wolters Kluwer Medknow Publications, 2018)
Congenital intestinal malrotation has a wide spectrum of presentation varying from incidental detection to recurrent episodes of benign abdominal pain to frank gastrointestinal obstruction, mid-gut volvulus, and bowel gangrene. Herein, we report the first case of congenital intestinal malrotation leading to gastric deserosalization. Intraoperative findings were conspicuous by the presence of midgut volvulus and gastric perforation in the posterior wall. There are a few more dimensions uncovered by this case, a brief reference to each has been considered necessary.